Analysis of Adaptive Interference Cancellation Using Common-Mode Information in Wireline Communications. (2007) - Magesacher Magesacher, Thomas Thomas; Ödling Ödling, Per Per; Börjesson Börjesson, Per Ola Per Ola
Abstract : Joint processing of common-mode (CM) and differential-mode (DM) signals in wireline transmission can yield significant improvements in terms of throughput compared to using only the DM signal. Recent work proposed the employment of an adaptive CM-reference-based interference canceller and reported performance improvements based on simulation results. This paper presents a thorough investigation of the cancellation approach. A subchannel model of the CM-aided wireline channel is presented and the Wiener solutions for different adaptation strategies are derived. It is shown that a canceller, whose coefficients are adapted while the far-end transmitter is silent, yields a signal-to-noise power ratio (SNR) that is higher than the SNR at the DM channel output for a large class of practically relevant cases. Adaptation while the useful far-end signal is present yields a front-end whose output SNR is considerably lower compared to the SNR of the DM channel output. The results are illustrated by simulations based on channel measurement data.